Exploring Canva Application to Write Announcement Text - Fitri Novia; Rachmanita; Gustina (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
One digital industrial technology of revolution 4.0 that may help students with their writing issues is Canva since this app can be an appealing and captivating medium to foster their writing. The purpose of this study was to determine whether writing achievement among students at SMP Negeri 1 Sungai Pinang who received instruction using the Canva App differed significantly from that of those who did not. The current research used a quasi-experimental design. The study’s samples included 66 students chosen using the purposive sampling method. Students were placed into two groups: experimental and control. A written test was used to collect the data which consisted of five topics. The result of the independent sample t-test found that the value of t-obtained was 10.897 at the significant level p<0.05 in two-tailed testing and the degree of freedom was 70, the critical t-table was 1.997. Since the value of t-obtained was higher than the critical value t-table (1.997) and ρ-value (0.00) lower than αvalue (0.05). The null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It indicated that students who were taught using the Canva App and those who were not had a significant difference in writing achievement abilities.